Fabrication of single-layered and double-layered TiO2 nanotube arrays for dye-sensitized solar cells - Sie, Dickson Aik Chee. (2013)
Advantages of titanium dioxide have allowed it to be a replacement to the conventional solar cells by the means of dye-sensitized solar cells (DSSCs). Nanotubular arrays have high surface-to-volume ratio, allowing a larger surface area to be dye-loaded to as compared to conventional nanocrystalline DSSC. Nanotubular arrays are more favourable to other structures due to its fast charge transport property that does not allow electron scattering and they promote light scattering within the structure. It is known that the efficiency of titanium dioxide nanotube arrays are affected by the geometrical aspects of the nanotubes, especially the length, diameter and compactness.